Chinese State Capitalism and the Transition to Digital Television in Africa - Abikanlu, Femi (Television in Africa in the Digital Age, 2021)
The transition to digital television referred to as the Digital Switchover (DSO) process or Digital Migration is an agreement of member countries of the International Telecommunications Union (ITU) at the Geneva Conference in 2006. The agreement requires changes to national spectrum allocation and redeﬁnes national participation in the global digital television and mobile telephony market. While the decision of most African states to embark on the digital migration programme remains independent, the policies and approach to the implementation were inﬂuenced by two dominant economic orthodoxies, the neoliberal free market (Becchio and Leghissa 2016; Johnson 2011; Overbeek and Apeldoorn 2012; Peters 2011) which promotes a media environment mainly driven by market imperatives and the Chinese State capitalism (Bremmer 2008; Gu et al. 2016; Lyons 2007; Szamosszegi and Kyle 2011; Xing and Shaw 2013) which is the economic ideology that drives the interventions of the Chinese government in the region’s digital migration.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; Chine (corpus analysé); Nigéria (corpus analysé); Nouvelle-Zélande/Aotearoa (lieu de production du savoir); _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé